Tarde venientibus ossa – For latecomers, the bones - Bartosiewicz, László (2009)
Archaeological excavators are latecomers by vocation, and given good preservation, much of the fi nds are animal bones. Taphonomy, the critical evaluation of bioarchaeological information in archaeology through understanding site formation processes, has become one of their chief tools in dealing with bone remains. A concept introduced in paleontology (Efremov 1940), taphonomy has not only become the indispensable fi rst step in archaeozoological inquiry, but also the best common denominator linking various studies of human-animal relationships across chronological periods and continents. This aspect of taphonomy is especially important in presenting geographically diverse areas with a rich and varied archaeological heritage such as the Neotropical region that includes what is historically known as Latin America and the southern United States around the Gulf of México. Immense latitudinal and altitudinal variability of habitats has made taphonomy the lingua franca between archaeozoologists - sometimes even within geographically varied countries such as Argentina (Gutiérrez et al. 2007). Párrafo extraído de la reseña a modo de resumen.